Morel-Lavallée Lesion with Chronic Osteomyelitis Mimicking Gynecomastia: Diagnostic Challenges in a Post-Trauma Case - Jason Clark Chen Tanujaya; Suprayitno Wardoyo (Green Publisher Indonesia, 2025)
A Morel-Lavallée Lesion (MLL) is a soft tissue injury caused by the sudden detachment of the skin and subcutaneous tissue from the underlying fascia, resulting in a closed degloving injury. It is often complicated by chronic osteomyelitis, which can present diagnostic challenges. We report a case of a 36-year-old male patient who developed an MLL with chronic osteomyelitis, initially mimicking gynecomastia. The patient presented with a mass in the chest area months after trauma, and clinical examination was inconclusive, with a history of diabetes mellitus and the lesion's proximity to the breast tissue complicating the differential diagnosis and raising suspicion for gynecomastia. However, a CT scan of the thorax revealed a MLL with underlying bone involvement, indicating chronic osteomyelitis. This case highlights the diagnostic challenges when typical findings may be misleading, emphasizing the need for comprehensive imaging and clinical correlation for accurate diagnosis and appropriate management.